Pertumbuhan dan Hasil Tanaman Sorgum Manis (Sorghum bicolor L.) dengan Aplikasi Pupuk Kandang di Lahan Kering - Samanhudi; Puji Harsono; Eka Handayanta; Rofandi Hartanto; Ahmad Yunus; Muji Rahayu; Wida S Anggara (Faculty of Agriculture University of Singaperbangsa Karawang, 2021)
Sorghum is include on grains but more widely used for livestock fodder. Sweet sorghum are often referred to as a raw materials for clean industry because almost all of the components of its biomass can be used for various industrial purposes. The aims of the research are to determine the effect of different types of manure on the growth and field of two varieties of sweet sorghum in dry land. The research method is a factorial experiment using Randomized Completely Block Design (RCBD), consists of two factors, which is sweet sorghum varieties and manure types. The varieties which was used are Numbu and Kawali. The second treatment which was used are without manure, chicken manure, goat manure, cow manure, and kascing. Total treatment combination is ten units and each combination repeated three times. The research variables are plant height, stem diameter, leaf number, leaf area, root length, root volume, fresh weight stover, dry weight stover, number of seeds, seed weight, essence content, and sugar content. Data were analyzed using F test with 95% of confidence level, if there is significantly a difference, and then followed by DMRT method in level of 5%. The result of this research shows that the highest sugar content is Kawali variety treatmented by chicken manure equals to 12.13 obrix. On the other hand, for lowest sugar level is Numbu variety treatmented by cow manure equals to 10.33 obrix. Interaction between types of manure and sweet sorghum varieties occurs in number of seeds per plant. Keywords: dry land, organic manure, sweet sorghum, Sorghum bicolor L.